2019
DOI: 10.1051/matecconf/201928308002
|View full text |Cite
|
Sign up to set email alerts
|

The Alpha stable distribution in ocean ambient noise modelling

Abstract: In view of the non-Gaussian of ocean ambient noise, the  stable distribution is applied to the statistical modelling. Firstly, the one-to-one correspondence between the four parameters of stable distribution and the sample mean, variance, skewness and kurtosis are established according to physical meaning. Then, numerical simulations are conducted to analyze the suitability of stable distribution for non-Gaussian ambient noise. In the case of white noise interference, noise is divided into Gaussian state, lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Among the parameters of the stable distribution, the parameter α is called the characteristic index, which determines the degree of the pulse characteristics of the distribution, the thicker the tail of the corresponding distribution, the larger the α value, the closer the distribution is to the Gaussian distribution, and the maximum α is 2. 26 The parameter β is called the symmetry parameter and is used to determine the slope of the distribution. β =0 corresponds to a symmetric distribution, abbreviated as SaS.…”
Section: Protection Levels Calculation Under Multi-parameter Stable O...mentioning
confidence: 99%
“…Among the parameters of the stable distribution, the parameter α is called the characteristic index, which determines the degree of the pulse characteristics of the distribution, the thicker the tail of the corresponding distribution, the larger the α value, the closer the distribution is to the Gaussian distribution, and the maximum α is 2. 26 The parameter β is called the symmetry parameter and is used to determine the slope of the distribution. β =0 corresponds to a symmetric distribution, abbreviated as SaS.…”
Section: Protection Levels Calculation Under Multi-parameter Stable O...mentioning
confidence: 99%
“…Existing underwater-acoustic-signal-processing methods may be invalidated under such non-Gaussian impulsive noise. To overcome this problem, several studies [16][17][18] have performed statistical analyses and models of non-Gaussian marine ambient noise. It was found that the generation and propagation of underwater impulsive noise are in accordance with the "heavy tail" statistical characteristics of the symmetric α-stable (SαS) distribution [19].…”
Section: Introductionmentioning
confidence: 99%
“…erefore, improved bispectrum methods which can be applicable to α-stable distribution environment need to be explored. Recently, α-stable distribution model was used for statistical modeling of the ocean environmental noise [31].…”
Section: Introductionmentioning
confidence: 99%